Restoration of blanket peat moorland delays stormflow from hillslopes and reduces peak discharge - Shuttleworth, Emma L.; Evans, Martin G.; Pilkington, Michael; Spencer, Thomas; Walker, Jonathan; Milledge, David; Allott, Timothy E.H. (Journal of hydrology: X, 2019)
Over the past 15 years there has been a proliferation of projects aiming to restore the structure and function of UK upland blanket mires, primarily by revegetation of bare peat and the blocking of erosion gullies. These restoration measures have potential to alter stormflow responses and contribute to Natural Flood Management, but their impacts on storm hydrographs are poorly quantified. This paper reports a before-after-control-intervention (BACI) study from three experimental headwater micro-catchments in the South Pennines (UK) representing the first rigorous experimental assessment of the impact of blanket peat restoration on catchment runoff. We evaluate the hydrological impacts of two standard restoration interventions; revegetation of bare peat, and revegetation of bare peat with additional gully blocking. Following revegetation there was a significant decrease in depth to water table and an increase in the prevalence of hillslope overland flow production. There were no significant changes in storm runoff coefficient following either restoration treatment. Storm hydrographs following revegetation had significantly longer lag times (106% increase relative to the control), reduced peak flows (27% decrease relative to the control), and attenuated hydrograph shapes. With the addition of gully blocking the effect is almost doubled. Lag times increased by a further 94% and peak flows reduced by an additional 24% relative to the control. We argue that the primary process controlling the observed changes in storm hydrograph behaviour is retardation of overland stormflow due to increased surface roughness. The significant changes to lag times and peak flow provide evidence that the restoration of degraded headwater peatlands can contribute to Natural Flood Management and the reduction of downstream flood risk, subject to wider catchment scale effects and sub-catchment storm hydrograph synchronicity. Keywords: Flood risk management, Natural flood management, Re-vegetation, Gully blocking, Water tables, Peatland hydrology